Price/time/intellectual efficiency of procurement: Uncovering the related factors in Chinese public authorities. Issue 3 (June 2020) - Wang, Qi; Zhang, Renjie; Liu, Junqi
Abstract: High efficiency is one of the important goals of public procurement (PP); however, research on PP efficiency is still not sufficient, especially in the context of developing countries. With a focus on the purchasing phase, this study measures three aspects of procurement efficiency of public authorities: price, time and intellectual efficiency. The relevant factors of these three aspects are explored and examined. 838 PP contracts in Chengdu city, China were collected in the first half of 2018 using a web crawler programme. Regression method is used to analyse the data. This study finds that the price efficiency of PP is negatively associated with the implementation of green public procurement (GPP) but is positively associated with the evaluation method (the weight of bidding price during evaluation) and the number of bidders. Time efficiency is negatively associated with GPP implementation. Intellectual efficiency is negatively associated with the size of the procurement. This study accomplishes the following: I. extends research to a still relatively unexplored context: developing countries; II. adds to the studies on public procurement efficiency; and III. investigates the influence of GPP implementation on PP efficiency in a developing country. Highlights: One of the pioneer studies on public procurement efficiency. Measuring the public procurement efficiency in three aspects. Examined and explored what factors are related to procurement efficiency. Explored the impact by Green Public Procurement (GPP). Introduced the procedure of public procurement with Chinese characteristics.